Dementia in a Black and minority ethnic population: characteristics of presentation to an inner London memory service. (August 2015) - Tuerk, Rosalyn; Sauer, Justin
Abstract : Aims and method: To examine data on referrals to an inner-city London memory service to explore any differences in referral rates, cognitive assessments and stages of dementia at presentation between ethnic groups. Results: African–Caribbean patients were well represented in the memory service. They were diagnosed with dementia on average 4.5 years younger than their White British counterparts and were more likely to be diagnosed with a vascular or mixed type dementia. However, scores on initial cognitive testing were significantly lower in the African–Caribbean group, possibly representing more advanced disease at presentation. Clinical implications: Initiatives to access Black and minority ethnic populations earlier in the course of their illness should be considered. Professionals need to consider the potential for cultural bias in memory testing and diagnosing dementia in these populations, and the importance of cultural competency in assessments.